The Role of Religious Beliefs and Practices in Disaster: The Case Study of 2009 Earthquake in Padang City, Indonesia - Adisaputri, Gianisa (Auckland University of Technology, 2016)
The number of disasters is increasing worldwide as the result of both the increase of hazards and people’s vulnerability. Vulnerability relates to the conditions of society making a hazard likely to turn into a disaster; and relates to social, economic and historical characteristics. Religious beliefs and practices, as one of the social characteristics embedded in society, influence people’s perceptions of risk and behaviours during disasters. Thus, religious beliefs and practices can be one factor of vulnerability to disasters. However, religious beliefs and practices also constitute a resource at individual and community level, potentially helping people bouncing back after disasters. To date, limited studies have investigated the role and significance of religious beliefs and practices in disasters. This current study attempts to fill this gap, using the 2009 earthquake in Padang City, Indonesia, as a case study. In 2009, a powerful earthquake struck Padang City, the capital city of West Sumatera province in Indonesia. The earthquake is considered one of the worst disasters to happen in Indonesia in the last 10 years. The recovery and reconstruction phases from the impact cost millions of dollars. Through this case study, this dissertation explores the effects of religious beliefs and practices towards disaster risk perceptions of the community in Padang city. It also examines the role of religious beliefs and practices in the way the community coped with disaster. The dissertation identifies the potential role of faith-based community in disaster risk reduction programmes. The present study relies on interviews conducted with two major religious community groups in Padang city, namely Muslims and Confucians. Data were collected from a total of eight participants, consisting of two religious leaders and two religious followers from each religion between April to May 2016. The study findings indicate that: 1) while religious beliefs can be a factor in people’s vulnerability towards risks and disaster perception, religious beliefs and practices can be one of the capacities that bind local communities together and contribute to successful coping with disasters; 2) with the discrepancies of relief distribution for two religious communities, religious communities can fill the gap that may exist from external intervention. Findings also indicate that religious beliefs and practices, combined with other mechanisms, should be integrated within disaster management and disaster risk reduction programmes as this would help build more resilient communities.
Keywords: Capacity; Community-based; Disaster; Religious beliefs and practices; Vulnerability